The language use of the Balinese diaspora in Kampung Bali, Penganjuran, a multilingual village in Banyuwangi - Ika Nurhayani; Sahiruddin Sahiruddin; Esti Junining; Hamamah Hamamah (Fakultas Sastra Universitas Negeri Malang, 2022)
The language use of the Balinese diaspora in Kampung Bali, Penganjuran, a multilingual village in BanyuwangiThe paper investigates the language use of the Balinese diaspora in Kampung Bali, Penganjuran, a multilingual village in Banyuwangi, which includes the multilingual situation, the nature of the language accommodation and the language domains. The current study answers the following research questions: (1) how is the situation of multilingualism in the village? (2) how is the situation of language accommodation in the Balinese village in the village? and (3) what are the domains of the use of the languages spoken in the village? The research applied a qualitative research approach using semi-structured interviews. Thirteen questions were asked during the interviews with three research participants. The answers were coded into data related to multilingualism situation, language accommodation, and domains of language use of the languages spoken in Kampung Bali, Penganjuran. The analysis aims to search for patterns and links in the coded texts. The findings show that the Balinese diaspora is the most multilingual ethnic group in Kampung Bali, Penganjuran, as they speak five languages: Indonesian, Balinese, Osing, Javanese, and Madurese. The Balinese also displays an accommodative nature toward the national language and the dominant vernacular languages. The findings also show that the domains of use of Balinese in the diaspora have declined since it is only used at the house of worship by three research participants and at home by one participant. The accommodative nature of the Balinese diaspora might have contributed to the shift from Balinese to the national language or to the dominant vernacular languages.Penggunaan bahasa diaspora Bali di Kampung Bali, Penganjuran, sebuah desa multilingual di BanyuwangiMakalah ini mengkaji penggunaan bahasa oleh diaspora Bali di Kampung Bali, Penganjuran, sebuah desa multilingual di Banyuwangi yang meliputi situasi multibahasa, sifat akomodasi bahasa dan domain bahasa orang Bali. Oleh karena itu penelitian ini menjawab pertanyaan-pertanyaan berikut ini: (1) bagaimana situasi multilingualisme di desa tersebut? (2) bagaimana situasi akomodasi bahasa di desa tersebut? (3) bagaimana ranah penggunaan bahasa Bali di desa tersebut? Makalah ini menggunakan metode penelitian kualitatif dengan wawancara semi terstruktur dengan 13 pertanyaan yang diajukan pada tiga responden penelitian. Jawaban-jawaban tersebut kemudian ditandai sesuai kaitannya dengan situasi multilingualisme, akomodasi bahasa, dan domain penggunaan bahasa dari bahasa-bahasa yang digunakan di Kampung Bali Penganjuran. Analisis bertujuan untuk mencari pola dan tautan dalam teks yang dikodekan. Temuan menunjukkan bahwa diaspora Bali adalah kelompok etnis yang paling multibahasa di Kampung Bali Penganjuran dengan berbicara lima bahasa, Indonesia, Bali, Osing, Jawa dan Madura. Orang Bali juga menampilkan sifat akomodatif terhadap bahasa nasional dan bahasa daerah yang dominan. Selanjutnya, temuan menunjukkan bahwa ranah penggunaan bahasa Bali pada diaspora mengalami penurunan karena hanya digunakan di rumah ibadat oleh tiga peserta penelitian dan di rumah oleh satu peserta. Sifat akomodatif dari diaspora Bali memiliki peranan dalam pergeseran dari bahasa Bali ke bahasa nasional atau ke bahasa daerah yang dominan.